STUDI ISOTOP OKSIGEN–18 DAN DEUTERIUM UNTUK MENENTUKAN LOCAL METEORIC WATER LINE(LMWL) DI DAERAH CIWIDEY DAN SEKITARNYA - Iwan Fahlevi Setiawan (PPSDM Geominerba, 2019)
Ciwidey is an area in the southern part of Bandung regency that has the potential for abundant natural resources, there is the potential for nature tourism, plantations, agriculture, geothermal, and if all the potential resources used maximally that will help development in Bandung regency and Ciwidey area especially. Average rainfall in the southern part of Bandung Metropolitan is 1500-4500 mm / yr, while the highest rainfall (3000-4500 mm / yr) is in the Southwest, namely in the magnification areas, such as Mount Patuha, Mount Powo, Mount Sumbul and Mount Kuda. This condition is interesting to be studied for the determination of Local Meteoric Water Line (LMWL). The method for determining LMWL is based on the analysis results of the stable isotope composition of 18O and 2H because rainwater isotopes have unique characteristics that are valued differently at each elevation. Rainwater sampling was carried out in 4 (four) different places, namely Ciwidey KUD with a height of 1114m above sea level (asl), Alamendah Village (1300m asl), Rancawalini (1770m asl) and Mount Patuha (1948m asl). The results of the stable isotope analysis of rainwater produce the local air meteoric equation in Ciwidey and its surroundings, namely δ2H = 7.55 δ18O + 12.06with R2= 0.990. This LMWL line equation can be used as a standard for determine recharge areawhich is very useful for groundwater management or geothermal management in Ciwidey area.